Research on the Application of Information Technology in Chinese Language Teaching in Primary Schools: Taking Excellent Traditional Chinese Culture as an Example - 杨, 洁 (Pacific International Journal, 2025)
The "Compulsory Education Chinese Curriculum Standards (2022 Edition)" explicitly states: "Chinese excellent traditional culture should be a key focus of instruction, further guiding students to absorb outstanding traditional cultures from both ancient and modern times, Chinese and foreign, thereby enhancing their ideological and cultural cultivation and fostering cultural confidence." Educating students in Chinese excellent traditional culture has become increasingly important, and the rapid development of information technology can further propel the advancement of Chinese language teaching in primary schools.However, there are certain issues in the process of integrating information technology into primary school Chinese teaching. For example, some teachers lack sufficient proficiency in applying information technology, school teaching resources lack systematic and targeted approaches, and the central role of students in learning is often overlooked. To address these problems, the following countermeasures are proposed: strengthening teachers' information technology training, emphasizing students as the main subjects of teaching, and guiding students to actively participate while applying information technology appropriately. Through these measures, the deep integration of information technology with the teaching of Chinese excellent traditional culture in primary school Chinese education can be promoted.